KEJAHATAN DUNIA MAYA (CYBERCRIME) DALAM PRESFEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Fitri, Aidil; Yusi, Suryani (Fakultas Hukum Universitas IBA Palembang, 2024)
Abstract The rise of Cyber ​​Crime with increasing technology which will cause a lot of harm to society must be accompanied by more massive law enforcement. Cybercrime, also known as cybercrime, is a form of crime that occurs in cyberspace via computers, mobile devices and internet networks. Cybercrime can attack anyone, not only individuals in society, but also government organizations. This action is very dangerous, so that it is not only regulated in Indonesian positive law, in Islam this action is a crime because it is an act of damage that harms many people.